The Effect of Financial Development on Convergence: Theory and Evidence* - Aghion, Philippe; Howitt, Peter; Mayer-Foulkes, David (Quarterly Journal of Economics, 2005)
We introduce imperfect creditor protection in a multicountry Schumpeterian growth model. The theory predicts that any country with more than some critical level of financial development will converge to the growth rate of the world technology frontier, and that all other countries will have a strictly lower long-run growth rate. We present evidence supporting these and other implications, in the form of a cross-country growth regression with a significant and sizable negative coefficient on initial per-capita GDP (relative to the United States) interacted with financial intermediation. In addition, we find that other variables representing schooling, geography, health, policy, politics, and institutions do not affect the significance of the interaction between financial intermediation and initial per capita GDP, and do not show any independent effect on convergence in the regressions. Our findings are robust to removal of outliers and to alternative conditioning sets, estimation procedures, and measures of financial development.